Pengaruh Pakan Egg Custard terhadap Laju Pertumbuhan Benih Ikan Mas (Cyprinus carpio) - Octoriani, Widyanti; Ayu, Hanandifa Meru Wisesa; Salsabilla, Nasywa; Sulistiani, Aliffah Ayu (Universitas Batangahari Jambi, 2026)
This study aimed to determine the effect of egg custard feed on the growth of common carp (Cyprinus carpio) fry. The experiment was conducted at the Integrated Laboratory of Universitas Tidar, Magelang City, Central Java, in July to August 2025 using a qualitative approach with data collected through experimental testing. Observed parameters included Survival Rate (SR), Absolute Weight Growth (Wm), Specific Growth Rate (SGR), and Feed Conversion Ratio (FCR). The results showed that egg custard feed provided better growth performance and survival compared to Artemia. The egg custard treatment achieved an SR of 100%, absolute weight growth of 10.1 g, SGR of 40.4%, and FCR of 7.92. In contrast, the Artemia treatment produced an SR of 60%, absolute weight growth of 3.1 g, SGR of 12.4%, and FCR of 15.69. These findings indicate that egg custard feed is more effective than Artemia in improving the growth and survival of common carp fry during the nursery phase. This formulated feed can serve as an alternative for common carp (Cyprinus carpio) culture and can potentially be applied to other cultured fish and shrimp species.